Dobutamine Induced Eosinophilic Myocarditis and Right Heart Failure Requiring Emergent Biventricular Assist Device Implantation. Issue 2 (March 2015) - Raje, Vikram P.; Lewis, Neil P.; Katlaps, Gundars J.; Quader, Mohammed A.; Shah, Keyur B.; Mankad, Anit K.
<x xml:space="preserve">Abstract</x> Dobutamine is a rare and unrecognized cause of eosinophilic myocarditis (EM). It is even more unique for it to cause significant clinical deterioration. Patients with end stage cardiomyopathy have very little cardiac reserve and dobutamine induced myocarditis may cause enough harm to require urgent mechanical circulatory support. We describe a man with dilated cardiomyopathy that developed accelerated clinical deterioration from dobutamine induced EM. He had a predominance of right heart failure, requiring an urgent biventricular assist device and acutely responded to withdrawal of dobutamine.